The Role of Spatial Frequency Information in Face Classification by Race - Zhang, Guoping; Wang, Zeyao; Wu, Jie; Zhao, Lun (Frontiers in Psychology, 2017)
It has been shown that face classification by race is faster for other-race than own-race faces (other-race classification advantage, ORCA). Controlling the spatial frequencies of face images, the present study pointed to perceptual processing differences between own-race and other-race faces that might account for the robust ORCA. Regardless of the races of the observers, the own-race faces were classified faster and more accurately for broad-band faces than for both lower and higher spatial frequency faces, whereas, although other-race faces were classified less accurately for higher spatial frequency than for either broad-band or lower spatial frequency faces, there was no difference between broad-band and lower spatial frequency conditions of other-race faces. Although it was not evident for higher spatial frequency condition, the ORCA was more evident for lower spatial frequency than that for broad-band faces. The present data indicate that global/configural information is needed for subordinate race categorization of faces and that an important source of ORCA is uncontrolled application of global/configural computations while seeing an own-race face but not while seeing an other-race face.